Body mass index limitation of overweight and obesity in Czech military personnel - Kupsová, Blanka; Pavlík, Vladimír; Fajfrová, Jana; Šafka, Václav; Lašák, Petr; Horáček, Jan M (Central European journal of public health, 2025)
OBJECTIVES: The first aim of this cross-sectional study was to reveal the prevalence of overweight and obesity among Czech military personnel (CMP). The second aim was to compare accuracy of the body mass index (BMI) classification with the body fat percentage (BF%), waist circumference (WC), and visceral fat area (VFA). BMI is a commonly used method to assess obesity, but its accuracy in reflecting body composition, especially in physically fit individuals, has been questioned. METHODS: Data were collected from six military units in the Czech Republic. Soldiers underwent anthropometric assessments including height, weight, WC, BF%, and VFA using the bioelectrical impedance method (BIA). RESULTS: The study group consisted of 446 soldiers (337 males, 109 females). The prevalence of obesity in Czech soldiers regardless of gender was 18%-20% according to BF% and 13%-16% according to WC. There were almost one fifth of obese males and more than 5% of females with BMI ≥ 30. The risk level of VFA was observed in 24% of male a 34% of female soldiers. In male soldiers there was a high rate (43%) of false positives according to BMI (BMI ≥ 25, BF% < 20), on the other hand, a certain part (18%) of female soldiers was classified as false negative according to BMI (BMI < 25, BF% ≥ 28). When overweight and obesity were assessed by WC and BMI, significant false positives (56%) were found in male soldiers (BMI ≥ 25, WC < 94). When obesity was evaluated using VFA and BMI, a certain rate of false negatives (30%) was found in female soldiers (BMI < 25, VFA ≥ 100). CONCLUSION: Through an analysis we explored the limitations of BMI, and we propose an alternative method (measurement of BF%, VFA using BIA) for a more accurate assessment of body composition in this specific population.
Keywords: obezita; visceral fat; Humans; index tělesné hmotnosti; Body Mass Index; ozbrojené síly; Overweight; složení těla; prevalence; Female; mladý dospělý; dospělí; Waist Circumference; lidé; body mass index; body composition; Military Personnel; Adult; ženské pohlaví; Male; Czech Republic; obvod pasu; Body Composition; Cross-Sectional Studies; Young Adult; Prevalence; Obesity; Česká republika; mužské pohlaví; military personnel; obesity; průřezové studie; nadváha